Mediation in the native courts of Sabah and Sarawak - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (IACLP 2014, 2014)
Mediation is an alternative dispute resolution mechanism process which is principally aimed at exploring options for amicable settlement of a dispute and to facilitate negotiations between the parties. Mediation is conducted in private settings by a neutral third party who is usually skilled, trained or experienced to mediate. Through this process, the disputing parties are able to speak among themselves, and work together to find a lasting common solution to their conflict under the guidance of the mediator. Undoubtedly, litigation in courts is costly, time-consuming with unpredictable outcomes and above all, it has the potential to damage irreparably the relationships between the parties. It must be noted that there are many disputes that need resolution outside the framework of conventional litigation. Having said the above, this article discusses the application of mediation in resolving customary disputes among the native of Sabah and Sarawak with particular reference to its practice in the native courts of the above mentioned states.